2015
DOI: 10.3389/fpsyg.2015.01660
|View full text |Cite
|
Sign up to set email alerts
|

Embodied cognition and circular causality: on the role of constitutive autonomy in the reciprocal coupling of perception and action

Abstract: The reciprocal coupling of perception and action in cognitive agents has been firmly established: perceptions guide action but so too do actions influence what is perceived. While much has been said on the implications of this for the agent's external behavior, less attention has been paid to what it means for the internal bodily mechanisms which underpin cognitive behavior. In this article, we wish to redress this by reasserting that the relationship between cognition, perception, and action involves a consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 57 publications
0
59
0
Order By: Relevance
“…Among human artefacts, including what most people would define as robots, the organisational closure condition is the major hurdle not yet leapt. This point has been recognised in the artificial intelligence literature, especially concerning "cognitive robotics" which emphasises embodiment [22,26]. For the time-being, it seems free-will, as defined here, is a unique property of living things, but the possibility of extending it to synthetic robots remains.…”
Section: Discussion and Synthesismentioning
confidence: 82%
See 1 more Smart Citation
“…Among human artefacts, including what most people would define as robots, the organisational closure condition is the major hurdle not yet leapt. This point has been recognised in the artificial intelligence literature, especially concerning "cognitive robotics" which emphasises embodiment [22,26]. For the time-being, it seems free-will, as defined here, is a unique property of living things, but the possibility of extending it to synthetic robots remains.…”
Section: Discussion and Synthesismentioning
confidence: 82%
“…According to most authors seeking to explain the apparent independence of action found among living systems, this requirement leads directly to constitutive autonomy, e.g., "every autonomous system is organizationally closed" (Varela [23], p. 58). This idea has a relatively long history in a multi-disciplinary literature (Froese et al [22], Zeleny [24], Rosen [25], Vernon et al [26], Bich [27] and references therein), but it is not clear if it is restricted to living systems, or may be broader. Therefore, rather than taking this literature as sufficient justification for a constitutive autonomy requirement, let us examine the options for matching with the following tasks:…”
Section: Systems With Causal Autonomymentioning
confidence: 99%
“…In the more traditional perspective of time, the cause is antecedent to the (consequent) effect and the flow runs linearly, whereas in the new paradigm of science, the causality and the relations between antecedents and consequences are recursive. 26 This paradigm highlights the rhythmic and mutual exchange between the environment and people, establishing patterns that are constantly changing and evolving into fields of self-organization. Thus, linear temporality does not exist, questioning the veracity of the analysis for the establishment of antecedents and consequences.…”
Section: /12mentioning
confidence: 99%
“…Likewise, Ziemke [92] and Vernon [93] provide somewhat visual approaches to modelling 'higher level' cognition. However, none of these visualization schemes aspires to provide a comprehensive pictographic language of the form described in this paper.…”
Section: Related Workmentioning
confidence: 99%